IMPLEMENTASI TUJUAN PENDIDIKAN DALAM MENINGKATKAN HASIL BELAJAR SISWA DI MTs PATRA MANDIRI PLAJU KOTA PALEMBANG - Ulfa Kesuma (Al-Tarbawi Al-Haditsah: Jurnal Pendidikan Islam, 2020)
This research is important to describe how the implementation of educational objectives in improving learning outcomes in MTs Patra Mandiri in Palembang. This study uses qualitative research methods and online methods. This study will discuss how the goals of national education, how the implementation of national education goals, the relationship between educational goals and learning outcomes, to the factors that influence learning outcomes. The results of this study are that the curriculum in MTs Patra Mandiri that includes Vision, Mission, Objectives, Planning, Implementation and Evaluation that has relevance to the elements of National Education Objectives include 1) Knowledge, 2) Understanding, 3) Habits, 4) Skills, 5) Appreciation, 6) Emotional, 7) Social relations, 8) Physical, 9) Ethical or moral, and 10) Attitudes. So that the purpose of education provides clear direction towards the implementation of learning and student learning outcomes.